A comparative investigation on direct carbon solid oxide fuel cells operated with fuels of biochar derived from wheat straw, corncob, and bagasse. (February 2019) - Qiu, Qianyuan; Zhou, Mingyang; Cai, Weizi; Zhou, Qian; Zhang, Yapeng; Wang, Wei; Liu, Meilin; Liu, Jiang
Abstract: A direct carbon solid oxide fuel cell (DC-SOFC) is an all-solid-state device that can directly convert the chemical energy of carbon into electricity with high efficiency and low pollution. This study assesses the feasibility of using carbon-rich biochar derived from wheat straw, corncob, and bagasse, respectively, as the fuels of DC-SOFCs. The chars are characterized using thermo-gravimetric analysis (TGA), scanning electron microscopy (SEM), energy dispersive spectrometer (EDS), X-ray diffraction (XRD), Raman spectroscopy, and tapping apparatus. Different quantities of K, Si, S, Ca, Mg, and Fe are found from the chars. It turns out that the output performances of the DC-SOFCs are closely related to the characteristics of the chars used. The peak power densities of 187 and 204 mW cm −2 at 800 °C are achieved by the cells with wheat straw char and corn cob char, whereas the cell with bagasse char performs the highest output performance of 260 mW cm −2 . Cells with 0.5 g chars of wheat straw, corn cob, and bagasse discharge at a constant current density of 140 mA cm −2, and it lasts for 15 h, 24 h and 22 h, respectively. The Boudouard reaction reactivity is assessed by analyzing the emitted gas compositions of DC-SOFCs discharging at a constant current density of 500 mA cm −2 via gas chromatography (GC). It turns out that the higher CO concentration representing the faster Boudouard reaction on the fuel. Graphical abstract: Image 1 Highlights: DC-SOFCs can operate on chars derived from wheat straw, corncob, and bagasse. Performances of the DC-SOFCs depend on characteristics of the chars. C, O, Mg, Si, P, S, Cl, K, and Ca are detected from the chars. K, Mg, and Ca can catalyze Boudouard reaction while S and Si deactivate it. With the highest yield, bagasse char gives the highest performance of its DC-SOFC.